Study of knowledge sharing behavior and online socialization in the i-class environment/ Syed Mohammed Alhady Syed Ahmad Alhady ... [et al.] - Syed Ahmad Alhady, Syed Mohammed Alhady; Zakaria, Azfahanee; Alawi Idris, Ahmad Sufi; Azmi, Nor Azlina; Noordin, Nazni; Mohamed Sawal, Mohd Zool Hilmie; Zakaria, Zaherawati (Faculty of Information Management, Universiti Teknologi MARA, 2012)
To ensure a full utilization of knowledge assets in an organization, Knowledge Sharing Behaviour methodology is basically the backbone and driving force behind the organizations' work processes. This study is to analyze the relationship between knowledge sharing behaviour and information exchange in the E-Learning Environment via i-Class from the ePJJ students of UiTM Kedah, Malaysia. Questionnaires were use to get information from the student such as Identification, online socialization, personal expectation. Correlation analysis use to find the relationship between variables.